Effect of strabismus surgery on refractive power of the eye - Hanan S Hegazy; Nashwa M Lamie; Rasha H Abd El Salam (Wolters Kluwer Medknow Publications, 2018)
Background The aim was to evaluate the refractive and corneal topographic changes occurring in the eyes after horizontal rectus muscle surgery, either unilateral recess-resect procedure or bilateral rectus muscle recession. Patients and methods A total of 31 eyes of 20 patients were included in this study. The patients underwent strabismus surgery for concomitant horizontal strabismus (exotropia). The patients were divided into two groups. Group A included nine patients (nine eyes), who were subjected to lateral rectus muscle recession and medial rectus resection in the same eye (R&R group). Group B included 11 patients (22 eyes) who were subjected to lateral rectus recession in both eyes (bilateral lateral rectus recession group). A full ophthalmic examination including cycloplegic automated refraction was carried out. Refraction and keratometry were assessed at 1-2 weeks preoperatively and 1 week, 1 month, and 3 months postoperatively. Corneal topography was performed before and 3 months after the operation. Preoperative and postoperative refraction was compared in terms of spherical equivalent (SE) and cylindrical power. Results The SE showed a transient statistically insignificant change toward the myopic side in the first week in both groups; these changes persisted for 2 months postoperatively and stabilized at the third month. However, the difference in SE from the preoperative values was statistically insignificant in both groups. Also, the changes in the refractive status that occurred when two muscles were operated in the same eye (R&R group) were greater than when only one muscle was operated. Conclusion Refractive status changed postoperatively, but this change was small and reversible.